Determinan Akuntabilitas Dana Desa Pada Pemerintahan Desa Di Kecamatan Beringin Kabupaten Deli Serdang - Yustika Yustika; Ratna Sari Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This study aims to determine the effect of Village Apparatus Competence, Community Participation and Internal Control System on Village Fund Accountability in Beringin District. This type of research is quantitative research. This research was conducted in 11 villages located in the District of Beringin. The population and sample in this study consisted of 55 people, each of which was the village head, village secretary, BPD village treasurer and the community of the 11 villages studied. The sampling technique used total sampling. Sources of data used in this study is primary data obtained by using a questionnaire and measured using a Likert scale. While the data analysis method used in this study is the method of multiple linear regression analysis carried out with the help of computer software, namely the Statistical Package for Social Science (SPSS 25). The results in this study indicate that: Village Apparatus Competence partially and significantly has no effect on Village Fund Accountability. Community participation partially and significantly has no effect on Village Fund Accountability. The Internal Control System partially and significantly affects Village Fund Accountability. Competence of Village Apparatus, Community Participation and Internal Control System simultaneously and significantly affect Village Fund Accountability.